Modeling positive systems using phase-type distributions: Modelación de sistemas positivos mediante distribuciones tipo fase - Rodríguez Esparza, Luz Judith (2026)
In this paper, we consider the relationship between phase-type distributions and positive systems through practical examples and applications. Phase-type distributions, commonly used in modelling dynamic systems, represent the temporal evolution of a set of variables based on their phase. On the other hand, positive systems, prevalent in a wide range of disciplines, are those where the involved variables maintain non-negative values over time. Through applications such as student trajectory dynamics and supply chain management, it is shown how phase-type distributions can be useful for describing and analyzing positive systems, offering insight into their dynamic behavior. Our main objective is to establish clear connections between these seemingly different concepts, highlighting their relevance and utility in various fields of study. The findings presented here contribute to a better understanding of the interaction between phase-type distribution theory and positive system theory, opening new opportunities for future research in this exciting interdisciplinary field.